Gender in Fairy tales and their Movie Adaptations - Váňa, David (Univerzita Pardubice, 2023)
This diploma thesis deals with the depiction of gender, gender roles, and gender stereotypes in fairy tales, namely their movie adaptations by Walt Disney Productions. The first chapter is dedicated to the history of the genre and its development. The diploma thesis introduces literary criticism, namely feminist literary criticism, which is fundamental for the analytical part of the thesis. Furthermore, the thesis elaborates on gender, gender roles, and gender stereotypes with respect to the primary source, fairy tales. The thesis provides an analysis of two fairy tales and their live-action remakes released by Walt Disney Productions. The diploma thesis aims to analyse what shift, if any, was accomplished in terms of the stereotypical depiction of gender roles in the live-action remakes of the animated versions of fairy tales.
Gender v pohádkách a jejich filmových adaptacích
Keywords: pohádky; gender; genderové stereotypy; Walt Disney; fairy tales; gender; gender stereotypes; Walt Disney